The influence of a child's age on the evaluation of smells and their hedonistic assessment - Brothánková, Pavlína; Vodička, Jan; Bažant, Jan (European journal of pediatrics, 2021)
Olfactory function in children is most commonly evaluated using the odour identification test despite the fact that it is difficult to properly name odorants for young children. The goal of this study was to evaluate the pleasantness rating of odorants by children. The participants were 182 healthy children: the first group included 63 girls and 59 boys (aged 6-7) and the second included 31 girls and 29 boys (aged 11-12). We assessed olfaction using (1) standard method of odorant identification using a U-Sniff test and (2) classifying the hedonic tone of the odorants into 5 categories. The identification test's median differed in younger and older groups of children; the median was 8 and 10 respectively (p < 0.01). The unpleasant hedonic tones were butter, fish and onion. The pleasant hedonic tones were apple, orange and peach. The younger usually categorised hedonic tones as pleasant, compared with the older children, who categorised the odorant's hedonic tones more often as neutral (p < 0.01).Conclusion: This study demonstrated that older children are able to identify odours better than younger ones. The categorisation of hedonic tones differed depending on the subject's age. The younger children tended to categorise odorants as being pleasant and older children as neutral. What is Known: • The test of odour identification is the most popular because it is reliable, practical, rapid and commercially available. • The ability to identify odours improves with age in children. What is New: • The categorisation of hedonic tones differs depending on age. The older children categorise odorants as being neutral significantly more often than younger children do.
Keywords: Hedonic; čich; Male; emoce; Child, Preschool; Odorants; Adolescent; Child; Odour pleasantness; U-Sniff test; Olfaction; Emotions; dítě; Motivation; mužské pohlaví; odoranty; mladiství; Smell; předškolní dítě; Children; lidé; motivace; ženské pohlaví; Humans; Female